(untitled) (Colombia Medica, 1981)
From February 1977 to August 1981 at the Hospital Universitario, Cali, Colombia, 35 patients with unstable dorsolumbar fractures were operated. In every case rod Harrington’s technique was used. Almost all of the patients (86%) were males. Among the patients with partial neurological deficit only two imparied after surgery; the remnant either improved or remained in the same condition. After the procedure a notorious improvement on spine angulation was observed. Infections, rather common in the first cases, decreased markedly after that surgery was performed more rapidly in the last operations.